(untitled) (International Journal of Innovative Technologies in Economy, 2018)
The article describes the econometric model of corporation income that was based on the statistics of relevant information of exchange markets and on the financial statements of the companies. The result was revealed the dependence of corporation revenue by indicators such as their market capitalization. The work presents recommendations for maximizing the corporation revenue that was based on the above indicators.